Short-term Investments in Dividend Paying Companies on the Warsaw Stock Exchange – Efficiency and Tax Shield Benefits for Individual Investors - Piotr DĄBROWSKI; Katarzyna JARNO (Communications of International Proceedings, 2021)
The article presents the results of short-term investments in dividend paying companies. We measured the investment efficiency of companies listed on the Warsaw Stock Exchange, one of the major capital markets in Central Europe. Usually, short-term trading for dividend purposes is ignored, as normally the dividend is treated as additional income in long-term trading strategies. We decided to test whether it is worth focusing on the dividend periods only, which actually means buying dividend shares and selling them as ex-dividend shares (‘overnight’ trading). The results take into account prices before and after the dividend is cut off as a comparison between theoretical and practical price changes. Additionally, specific rules of taxation governing dividend and speculative operations are included in the results.
Keywords: short-term trading; investments; dividend companies; capital market taxation